Molecular characterization of Selar crumeenophthabnus (ikan Lolong), Decapterus 111aruadsi (ikan Sadin) and Rastrelliger kanagurta (ikan kembong hitatn) fish species using mtDNA COI gene (DNA barcoding) - Kee, Loo Suet (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
This study was undertaken to design a set of common primers to amplify the mitochondria DNA (mtDNA) cytochrome coxidase subunit I (COl) barcoding region of marine fish species. The primer set namely: forward primer (ST F I) "CAC AAA GAC ATC GGC ACCC" and the reverse primer (ST R3) "AAG AAT CANG AAT AG/AG TOT TG" were able to amplify the three species chosen for this study. The sequence data generated were compared and analysed using the sequence of mtDNA COl gene of Gobio gobio (GenBank accession no.: AB239596) as reference. On analysis, about 20% polymorphic positional variations were detected across the three species. The sequence data generated were used to study their phylogenetic relationship by constructing a rooted neighbor joining (NJ) dendrogram